(untitled) - American Society of Civil Engineers (Bruce Gossett, 2009)
The present study aims at the application of the hybrid model, which consist of artificial neural network and fuzzy logic in the reservoir operating policy during critical periods. The proposed hybrid model combines the learning ability of artificial neaural networks and the transparent nature of fuzzy logic.
Keywords: Water resources development,Water,Phát triển tài nguyên nước,Nước; Periodicals,Ấn phẩm định kỳ